2017
DOI: 10.1111/cpf.12448
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐ and inter‐day reproducibility of low‐flow mediated constriction response in young adults

Abstract: Vasoconstriction to low-flow conditions influences the subsequent maximal dilation during reactive hyperaemia. However, L-FMC is variable as evidenced by the weak intra- and interday reproducibility of the measure. Further research should study brachial L-FMC reproducibility among varying populations and the implications L-FMC has on the interpretation of FMD results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Endothelial function in upper‐limb arteries does not reflect endothelial function in the popliteal artery (O'Brien et al, 2019a; Thijssen et al, 2008). The interactions between upper‐limb L‐FMC and FMD responses are controversial (Gori et al, 2010, 2012, 2017; Harbin et al, 2017; Harrison et al, 2011; Irace et al, 2016; Spiro et al, 2011). However, the results of the present study are consistent with Spiro et al (2011) who observed a negative relationship between brachial artery L‐FMC and FMD in healthy adults, but extends these observations to the popliteal artery and establishes the independent association between these measures of endothelial vasomotor function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endothelial function in upper‐limb arteries does not reflect endothelial function in the popliteal artery (O'Brien et al, 2019a; Thijssen et al, 2008). The interactions between upper‐limb L‐FMC and FMD responses are controversial (Gori et al, 2010, 2012, 2017; Harbin et al, 2017; Harrison et al, 2011; Irace et al, 2016; Spiro et al, 2011). However, the results of the present study are consistent with Spiro et al (2011) who observed a negative relationship between brachial artery L‐FMC and FMD in healthy adults, but extends these observations to the popliteal artery and establishes the independent association between these measures of endothelial vasomotor function.…”
Section: Discussionmentioning
confidence: 99%
“…Tracking the lumen diameter throughout the ischemic period is recommended by FMD guidelines (Thijssen et al, 2011a). Research in upper-limb arteries (ie brachial or radial) have reported conflicting findings, with a larger L-FMC response being associated with a smaller FMD (Harbin et al, 2017;Harrison et al, 2011;Irace et al, 2016), larger FMD (Gori et al, 2017;Spiro et al, 2011) or no relationship with FMD (Gori et al, 2010(Gori et al, , 2012Spiro et al, 2011). Although both FMD and L-FMC are mediated by changes in shear-stress, they involve different vascular smooth muscle signalling mechanisms, which may support a lack of relationship between them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation